2016
DOI: 10.1186/s12879-016-1582-3
|View full text |Cite
|
Sign up to set email alerts
|

Dirofilaria repens microfilariae from a human node fine-needle aspirate: a case report

Abstract: BackgroundHuman dirofilariosis is still a little known infection even in endemic areas. Dirofilariosis is zoonotic infection usually abortive in humans; instead, we report a very rare case (the 4th in the world), the first in Italy, in which at least two infective larvae became mature adults that mated and produced active microfilariae even though they did not reach peripheral blood.Case presentationA 30-year-old Italian woman presented with a transient oedematous swelling on the left abdominal wall with a cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Fontanelli Sulekova et al 2016). The sample from the patient 2 shared 99% identity with deposited sequences from D. repens.…”
Section: Resultsmentioning
confidence: 90%
“…Fontanelli Sulekova et al 2016). The sample from the patient 2 shared 99% identity with deposited sequences from D. repens.…”
Section: Resultsmentioning
confidence: 90%
“…Later, similar results were obtained in Italy. A case was reported in which microfilariae were detected in the fine-needled aspirate of a Dirofilaria subcutaneous node [38]. It was confirmed that complete development and fertilization of D. repens worms in human hosts might occur [38].…”
Section: Detection and Diagnosis Of Human Dirofilariasis Casesmentioning
confidence: 87%
“…A case was reported in which microfilariae were detected in the fine-needled aspirate of a Dirofilaria subcutaneous node [38]. It was confirmed that complete development and fertilization of D. repens worms in human hosts might occur [38]. In the following years, microfilariae were detected in the blood of a patient [5,39,40], such as in Europe, where 10 cases of D. repens were found in the lung; two similar cases were described in Russia as well [41].…”
Section: Detection and Diagnosis Of Human Dirofilariasis Casesmentioning
confidence: 99%
“…Several authors have discussed the obligate and facultative relationships between human and the dirofilariasis pathogen Dirofilaria (Nochtiella) repens infection [1] , as well as the role of the human as a potential source of this roundworm infection in nature [1] , [2] . This hypothesis is based on the cases of detection of larvae, adult, and gravid females of D. repens in subcutaneous nodes [3] . Russian literature described the case where D. repens larvae detected in human peripheral blood [2] , [4] .…”
Section: Introductionmentioning
confidence: 99%